2005
DOI: 10.1093/occmed/kqi048
|View full text |Cite
|
Sign up to set email alerts
|

Increased cancer risk among surgeons in an orthopaedic hospital

Abstract: These findings caution against surgeons' underestimation of the potential radiation risk and insufficient promotion of safe work practices by their health care institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
202
0
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(218 citation statements)
references
References 0 publications
2
202
0
14
Order By: Relevance
“…However, the total surgical Recent studies have demonstrated significant increases in malignancy rates caused by exposure to X-ray radiation in surgeons who perform orthopedic, urological or neurosurgery procedures (7,18,21,22,29). In spite of the reductions in the risk of radiation exposure by the use of lead-containing vests and lead panels in the operating room, the risk can never be reduced to zero.…”
Section: Resultsmentioning
confidence: 99%
“…However, the total surgical Recent studies have demonstrated significant increases in malignancy rates caused by exposure to X-ray radiation in surgeons who perform orthopedic, urological or neurosurgery procedures (7,18,21,22,29). In spite of the reductions in the risk of radiation exposure by the use of lead-containing vests and lead panels in the operating room, the risk can never be reduced to zero.…”
Section: Resultsmentioning
confidence: 99%
“…Mastrangelo et al [12] suggested that orthopaedic surgeons in a hospital with poor radiation protection had a substantially greater incidence of cancer. The concern regarding the effects of radiation exposure has led to the use of ALARA (as low as reasonably achievable) techniques with healthcare workers [7].…”
Section: Introductionmentioning
confidence: 99%
“…The delayed radiation exposure effect from this type of exposure is not trivial [25,28,34]. In 2005, Mastrangelo [19] reported orthopaedic surgeons have a fivefold increase in their lifetime of cancer rates compared with nonorthopaedic surgeons in a hospital setting.…”
Section: Introductionmentioning
confidence: 99%